Negara Ideal dalam Pemikiran Fundamentalis Islam - sukri, mhd alfahjri (POLITEA, 2021)
This research aims to explain the problem of Islamic fundamentalism and analyze the thoughts of Islamic fundamentalist figures, namely Abul A'la Al-Maududi, Hasan Al-Banna, and Taqiyuddin An-Nabhani about the ideal state. Qualitative methods are used in this research with data obtained through books, journals, scientific articles, and other related sources. The results showed that the ideal country according to the thoughts of Abul A'la Al-Maududi, Hasan Al-Banna, and Taqiyuddin An-Nabhani is a country based on Islam. These figures made Rasulullah when he founded the state of Medina until the time of Khulafaur Rasyidin as the reference for the ideal state. Because for them, at that time Islam was used as the main reference and foundation of life and could solve all problems, including problems in living as a state. These figures also reject the separation between religion and state (secularism), and agree to make sovereignty in God's hands. According to them, religion has an important role in the state. In addition, they also placed Ahlul Halli wal Aqdi  as an important part of an Islamic state.This research aims to explain the problem of Islamic fundamentalism and analyze the thoughts of Islamic fundamentalist figures, namely Abul A'la Al-Maududi, Hasan Al-Banna, and Taqiyuddin An-Nabhani about the ideal state. Qualitative methods are used in this research with data obtained through books, journals, scientific articles, and other related sources. The results showed that the ideal country according to the thoughts of Abul A'la Al-Maududi, Hasan Al-Banna, and Taqiyuddin An-Nabhani is a country based on Islam. These figures made Rasulullah when he founded the state of Medina until the time of Khulafaur Rasyidin as the reference for the ideal state. Because for them, at that time Islam was used as the main reference and foundation of life and could solve all problems, including problems in living as a state. These figures also reject the separation between religion and state (secularism), and agree to make sovereignty in God's hands. According to them, religion has an important role in the state. In addition, they also placed Ahlul Halli wal Aqdi  as an important part of an Islamic state.